Sistem Pendukung Keputusan Penerima Bantuan Covid-19 Kelurahan Bugel Kota Salatiga Menggunakan Simple Additive Wieghting (Saw) - Ria Saskia Zevanya Warami (Journal of Computer and Information Systems Ampera, 2021)
The purpose of this study is to facilitate decision making in providing COVID-19 assistance to underprivileged communities in Bugel Village, Salatiga City. This study uses the Simple Additive Wieghting method or commonly referred to as the weighted addition method. This method performs a weighted summation of the performance ratings of each alternative on all attributes. The results of the study from 5 families showed who was the most eligible to receive the Covid-19 assistance in the Bugel Village, Salatiga City, namely Sardianto with a final normalization result of 0.785. It is hoped that this research can be used to make decisions quickly and objectively